Classroom Clickers Offer More than Repetition: Converging Evidence for the Testing Effect and Confirmatory Feedback in Clicker-Assisted Learning - Amy Shapiro (Journal of Teaching and Learning with Technology, 2013)
The present study used a methodology that controlled subject and item effects in a live classroom to demonstrate the efficacy of classroom clicker use for factual knowledge acquisition, and to explore the cognition underlying clicker learning effects. Specifically, we sought to rule out repetition as the underlying reason for clicker learning effects by capitalizing on a common cognitive phenomenon, the spacing effect. Because the spacing effect is a robust phenomenon that occurs when repetition is used to enhance memory, we proposed that spacing lecture content and clicker questions would improve retention if repetition is the root of clicker-enhanced memory. In experiment 1 we found that the spacing effect did not occur with clicker use. That is, students performed equally on clicker-targeted exam questions regardless of whether the clicker questions were presented immediately after presentation of the information during lecture or after a delay of several days.  Experiment 2 provided a more direct test of repetition, comparing test performance after clicker use with performance after a second presentation of the relevant material. Clicker questions promoted significantly higher performance on test questions than repetition of the targeted material. Thus, the present experiments failed to support repetition as the mechanism driving clicker effects. Further analyses support the testing effect and confirmatory feedback as the mechanisms through which clickers enhance student performance. The results indicate that clickers offer the possibility of real cognitive change in the classroom.